\(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}=\frac{1}{a+b+c}\)
\(\Leftrightarrow\frac{ab+bc+ca}{abc}=\frac{1}{a+b+c}\)
\(\Rightarrow\left(ab+bc+ca\right)\left(a+b+c\right)=abc\)
\(\Leftrightarrow ab^2+a^2b+ac^2+a^2c+bc^2+b^2c+2abc=0\)
\(\Leftrightarrow ab^2+a^2b+ac^2+bc^2+a^2c+abc+b^2c+abc=0\)
\(\Leftrightarrow\left(a+b\right)ab+c^2\left(a+b\right)+bc\left(a+b\right)+ac\left(a+b\right)=0\)
\(\Leftrightarrow\left(a+b\right)\left(c^2+ab+bc+ac\right)=0\)
\(\Leftrightarrow\left(a+b\right)\left(b+c\right)\left(c+a\right)=0\)
Vậy ta có các trường hợp: \(a=-b,c=0\)hoặc \(b=-c,a=0\)hoăc \(a=-c,b=0\).
Với từng trường hợp ta đều có đpcm.